Implementasi Keperawatan Manajemen Nyeri Masalah Nyeri Akut Pasien Pasca Bedah Benigna Prostat Hiperplasia - Mediarti, Devi; Sashabila, Alaika; Syokumawena, Syokumawena (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: Benign Prostate Hyperplasia (BPH) is a common problem in men because they often hold urine when they want to urinate, and this causes increased enlargement of the prostate gland. The procedure for Benign Prostate Hyperplasia (BPH) sufferers is surgery. Surgical procedures usually have side effects that are definitely felt by patients undergoing surgery, one of which is pain. Objective: This case study is to provide deep breathing relaxation therapy to reduce the level of pain in patients after surgery for benign prostate hyperplasia at Siti Fatimah Regional Hospital, Palembang. Method: This research uses descriptive methods in the form of a case study. The approach used is a nursing care approach which includes assessment, nursing diagnosis, planning, implementation and evaluation. The subjects in this study were 2 people with the same criteria, namely patients after surgery for benign prostate hyperplasia. Results: Research shows that by providing deep breathing relaxation therapy, the pain scale for Mr. Y and Mr. A decreased. Conclusion: The deep breathing relaxation therapy technique is a non-pharmacological therapy to treat pain in patients after surgery for benign prostate hyperplasia. This nursing action can be an intervention to reduce the acute pain felt by the patient